2021
DOI: 10.3390/pr9020279
|View full text |Cite
|
Sign up to set email alerts
|

Coarse-Grain DEM Modelling in Fluidized Bed Simulation: A Review

Abstract: In the last decade, a few of the early attempts to bring CFD-DEM of fluidized beds beyond the limits of small, lab-scale units to larger scale systems have become popular. The simulation capabilities of the Discrete Element Method in multiphase flow and fluidized beds have largely benefitted by the improvements offered by coarse graining approaches. In fact, the number of real particles that can be simulated increases to the point that pilot-scale and some industrially relevant systems become approachable. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(35 citation statements)
references
References 107 publications
0
35
0
Order By: Relevance
“…Each CGP represents the movement of W (statistic weight) physical particles and these particles share the same properties, such as mass, velocity, and positions. The derivation and validation of CG‐DEM is available in the literature 12–15 . The selection of statistic weight influences the computation cost and the accuracy of the simulation.…”
Section: Computational Fluid Dynamic Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each CGP represents the movement of W (statistic weight) physical particles and these particles share the same properties, such as mass, velocity, and positions. The derivation and validation of CG‐DEM is available in the literature 12–15 . The selection of statistic weight influences the computation cost and the accuracy of the simulation.…”
Section: Computational Fluid Dynamic Modelsmentioning
confidence: 99%
“…Recently, the coarse‐grained discrete element method (CG‐DEM) reduced the computation cost of discrete simulations by lumping physical particles into numerical parcels. It was used in the simulation of coal gasification, 6,7 biomass gasification, 8 biomass pyrolysis, 9 methanol‐to‐olefin, 10 circulating fluidized bed (CFB) carbonator, 11 and many other reactors 12 . However, its capability to accurately predict the elutriation rate was not evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we employed the standard values of 2/7 and 1/2 for the ratios between the normal and tangential values of the spring constant and restitution coefficient. Both Fluent and MFiX allow for reducing the number of particles by lumping several of them in a larger "parcel"; this approach is usually known as "coarse-graining" [42,43]. As the number of involved particles is already quite low, this procedure was not employed here.…”
Section: Simulation Setupmentioning
confidence: 99%
“…Although these three models indicated that the particle behavior in fluidized beds could be represented, and that the calculation load could be reduced, the particle behavior cannot be represented with sufficient accuracy. Subsequently, for fluidized beds, numerous coarse-grain models have been developed to improve the accuracy and versatility of the models [17][18][19][20][21][22][23][24]. Sakai et al proposed the more accurate coarse-grain model for the particle behavior in fluidized beds.…”
Section: Introductionmentioning
confidence: 99%